Long noncoding RNA expression profiling in cancer: Challenges and opportunities. Issue 4 (20th January 2019) - Lorenzi, Lucía; Avila Cobos, Francisco; Decock, Anneleen; Everaert, Celine; Helsmoortel, Hetty; Lefever, Steve; Verboom, Karen; Volders, Pieter‐Jan; Speleman, Frank; Vandesompele, Jo; Mestdagh, Pieter
Abstract: In recent years, technological advances in transcriptome profiling revealed that the repertoire of human RNA molecules is more diverse and extended than originally thought. This diversity and complexity mainly derive from a large ensemble of noncoding RNAs. Because of their key roles in cellular processes important for normal development and physiology, disruption of noncoding RNA expression is intrinsically linked to human disease, including cancer. Therefore, studying the noncoding portion of the transcriptome offers the prospect of identifying novel therapeutic and diagnostic targets. Although evidence of the relevance of noncoding RNAs in cancer is accumulating, we still face many challenges when it comes to accurately profiling their expression levels. Some of these challenges are inherent to the technologies employed, whereas others are associated with characteristics of the noncoding RNAs themselves. In this review, we discuss the challenges related to long noncoding RNA expression profiling, highlight how cancer long noncoding RNAs provide new opportunities for cancer diagnosis and treatment, and reflect on future developments.